Gestão de pessoas se faz também com atores não-humanos - Silva, Elisandra dos Santos (2022)
It is important to realize that organizational structures are part of a network of human and nonhuman actors, which include the organization itself, as well as its resources, collaborators, inputs, and even the environment where it is inserted and its competitors, forming a large sociotechnical network. Thus, the basic argument of the present research is that people and objects share ideas, experiences and opinions in their daily environment and within their work environment they establish formal and informal relationships, values, beliefs that modify their way of thinking and acting. These actors and their connections form the networks woven by them, which encompass knowledge, technologies and information. As a result, the objective of the dissertation was to analyze the relationships, flow and work routines of the People Management Pro-Rectory at the State University of Paraíba through the eyes of sociotechnical networks. In theoretical terms, it was based on sociomateriality and Actor-Network Theory, also known as Sociology of Associations, approaching the concept of social linked to human and non-human actors and considering social aggregates as something to be explained through associations. Methodologically, it is an empirical research that used post-qualitative research as a method, the ethnography of sociotechnical networks for the collection and analysis of data and, for the organization and understanding of the flow and webs that form the sociotechnical network of People Management Pro-Rectory, participant observation was used. The investigation, through the mapping of the sociotechnical network, identified the existing arrangements and links between the actors – human and non-human – of the Pro-Rectory. It was also found that the performances of individuals and artifacts influence - and can interfere - in organizational results, as they are linked to political, collaborative, technical, technological, communication and media actions that encompass the entire administrative structure of the Pro- Rectory. This understanding reveals the need to think about the organization in a holistic and systemic way, in a post-humanist view, in which organizational practices are shaped by the bonds, agencies and performances of people and objects/things. In general, it was noticed that these associations bring to light the inseparability between people and artifacts, since people management is also done with non-human actors.